Outcome of early laparoscopic cholecystectomy versus delayed laparoscopic cholecystectomy for patients with acute cholecystitis - Rather, Zahid Mohd; Majid, Nighat Ara; Islam, Mohd Nazrull; Mohd, Raja Waseem (International Surgery Journal, 2020)
Background: This prospective randomized study was undertaken to to assess the outcomes of early versus delayed cholecystectomy for patient’s acute cholecystitis. Methods: 70 patients with acute cholecystitis were prospectively randomized to either an early laparoscopic cholecystectomy (n=35) or a delayed laparoscopic cholecystectomy group (n=35). The mean operative time, conversion rate, total hospital stay, intra-operative and post-operative complications, average hospital cost were evaluated between the two groups. Results: A total of 70 patients were enrolled, 35 patients in each group. There was no significant difference in the conversion rates (early, 8.57% vs delayed, 5.71%) and postoperative complications (early, 25% vs delayed, 20%). At the cost of an increased operating time (early, 81 minutes vs delayed, 78 minutes) and blood loss (early, 180.33ml vs delayed, 108.00 ml), early laparoscopic cholecytectomy significantly shortened the total hospital stay (early, 1.5 days vs. delayed, 7.95 days) and average hospital cost (early 9240 INR vs delayed, 12251 INR). Conclusions: The safety and efficacy of early and delayed laparoscopic cholecystectomy for acute cholecystitis were comparable in terms of morality, morbidity and conversion rate. However early laparoscopic cholecystectomy allows significantly shorter total hospital stay and reduction in days away from work at the cost of longer operating time and blood loss and offers definitive treatment at initial admission. Moreover it avoids repeated admissions for recurrent symptoms has both medical as well as socioeconomic benefits and should be the preferred approach for patients managed by surgeons with adequate experience in laparoscopic cholecystectomy.